2022
DOI: 10.1177/01655515221081353
|View full text |Cite
|
Sign up to set email alerts
|

A web-based information intervention for family caregivers of patients with Dementia: A randomized controlled trial

Abstract: This study aimed to evaluate the efficacy of a web-based health information intervention on knowledge, care burden and attitudes of family caregivers of patients with dementia. This study is a unblinded randomised controlled trial. The study population consisted of family caregivers of patients with dementia ( n = 50) which were randomly allocated to the intervention group (access to the web-based health information) or control group (access to information as usual). The participants completed knowledge, care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The studies on web-based programs for caregivers of chronic patients reported that the caregivers described the use of this method as easy, useful, and practical, and con rmed the positive outcomes on knowledge, attitude, self-e cacy, and feelings of sympathy, and reducing stress and anxiety in caregivers. The caregivers also reported that they felt more con dent about their care skills and communication with their patients (42). One of the advantages of the current study was the implementation of a web-based support program.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The studies on web-based programs for caregivers of chronic patients reported that the caregivers described the use of this method as easy, useful, and practical, and con rmed the positive outcomes on knowledge, attitude, self-e cacy, and feelings of sympathy, and reducing stress and anxiety in caregivers. The caregivers also reported that they felt more con dent about their care skills and communication with their patients (42). One of the advantages of the current study was the implementation of a web-based support program.…”
Section: Resultsmentioning
confidence: 92%
“…Salehi Nejad et al (2017) investigated the effect of providing web-based health information on the care burden of family caregivers of patients with dementia and showed that after the intervention, the care burden of the participants in the intervention group decreased signi cantly, while no change was observed in the care burden of the participants in the control group (42). These results con rmed the effectiveness of the interventions for providing health information and necessary counseling and training on caring for these patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of knowledge concerning technology and the internet continue to be serious barriers in virtual interventions [ 32 ]. To address these barriers, our study staff purchased equipment, provided participants with iPads® and internet access if needed, and supplied training and easy-to-follow materials with pictures and descriptions for accessing all aspects of our virtual platform and intervention, including closed-captioning on all YouTube exercise videos.…”
Section: Discussionmentioning
confidence: 99%
“…There are different methods to provide PR education to the FCs of patients with COPD, including face-to-face (FTF) education, web-based education, and smartphone-based education [ 14 ]. FTF education is the standard method for education [ 15 ].…”
Section: Introductionmentioning
confidence: 99%